Humanitarian giftedness - Sternberg, Robert J; Rodríguez-Fernández, María Isabel (Gifted Education International, 2023)
Humanitarian giftedness is the deployment of one’s gifts and talents in a way that, at some level, benefits humanity. Humanitarian giftedness involves sharing one’s gifts with others in a way that makes the world a better place. It is not something people are born with—they develop it in the same way other forms of expertise are developed—through a deployment of abilities as developed by deliberate practice and a focus on giving rather than just receiving. Teachers and parents can develop humanitarian giftedness by being role models, by sharing stories of humanitarian giftedness, and by encouraging it in their students. They also must discourage use of gifts for ends that harm humanity. The road to more humanitarian deployment of gifts is not through tests and other assessments, but through the development of humanitarian gifts as a learned form of expertise—as gifts not from genes, but rather from the interaction of the person with the tasks they confront and the environmental contexts in which they live.
Keywords: giftedness; humanitarian giftedness; narcissism; role-modeling; transformational giftedness; Scopus